HUKUM TRADISIONALYANG BERBASIS AGAMA - Santi Marlina; Eci Fitri Yunika; Dedi Rinaldo; Risky Hardian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Traditional law based on religion has long served as a legal system governing social and cultural life in certain societies. This study aims to analyze the implementation of traditional law based on religious teachings in society, as well as to explore how this law interacts with modern state legal systems. Using a qualitative approach with a case study method, this research examines adat law in Aceh, which is based on Islamic teachings, and the role of religious leaders in its enforcement. The findings indicate that traditional law based on religion in Aceh remains relevant in resolving social disputes, but faces challenges in its application alongside state law. In this context, religious law functions as a mechanism to uphold moral and social values, although at times it conflicts with formal legal regulations. This study concludes that, despite the tensions between traditional law and state law, religion-based traditional law continues to play an important role in creating social justice and cultural sustainability in society.